Multiplexed measurements of salivary fetuin-A, insulin, and adiponectin as potential non-invasive biomarkers in childhood obesity. (May 2022) - Selvaraju, Vaithinathan; Babu, Jeganathan R.; Geetha, Thangiah
Highlights: Salivary fetuin-A and insulin was significantly increased, and adiponectin was decreased in obese compared to normal weight. Fetuin-A and insulin showed the highest area under the curve with excellent diagnostic accuracy than adiponectin. Fetuin-A and insulin showed a positive correlation with obesity measures, while adiponectin was inversely associated. Abstract: Background: Obesity increases the risk of developing insulin resistance, diabetes, and cardiovascular disease. The current study is designed to evaluate the association of salivary fetuin-A, insulin, and adiponectin with the obesity measures in children. Methods: Seventy-six children aged 6–10 years participated in the study. Anthropometric measurements were recorded, and saliva was collected from the participants. Based on the Center for Disease Control and Prevention (CDC), the participants were classified into normal weight (NW), overweight (OW), and obese (OB). Multiplex analysis for salivary markers fetuin-A, insulin, and adiponectin was performed using Luminex performance assay. The diagnostic value of the salivary marker was identified by receiver operating characteristics (ROC) curve, the correlation between obesity measures and markers were performed by regression analysis. Results: Salivary fetuin-A and insulin were significantly increased in OW and OB in comparison to NW. Adiponectin was significantly decreased in the OB compared to NW and OW groups. Fetuin-A and insulin had the highest area under the curve with the best diagnostic value of a biomarker than adiponectin. Fetuin-A and insulin showed a positive association with obesity measures and among the parameters, but adiponectin was inversely associated. Conclusions: Salivary fetuin-A, insulin, and adiponectin levels are associated with the obesity in elementary school-aged children.